MANAJEMEN KESISWAAN DALAM MENINGKATKAN ETOS KERJA ORGANISASI SISWA INTRA SEKOLAH (OSIS) DI SMK FATAHILLAH CILEUNGSI - Royandi, Muhamad Adnan; Irhamsyah, Fahmi; Sudjana, Dace (Institut Nahdlatul Ulama Tasikmalaya, 2024)
Student management can be applied to OSIS whose work ethic needs to be continuously improved because it can help achieve school goals. Increasing the work ethic of OSIS administrators can be achieved through planning, coaching and training. This research aims to: find out student management planning and coaching and training in improving the work ethic of the OSIS, as well as knowing the impact of this management in improving the work ethic of the OSIS of SMK Fatahillah Cileungsi. This research uses a qualitative approach. Data collection in this research used interviews, observation and documentation. The results of this research explain that student management in improving the work ethic of the OSIS at Fatahillah Cileungsi Vocational School is: 1) Student management planning is carried out by holding school work meetings, socializing the program to all OSIS administrators, forming an activity committee, and making a final activity report, 2) Student development and training is carried out by holding LDKS activities, involving OSIS administrators in OSIS forums throughout West Java, collaborating with all extracurricular activities, and carrying evaluation once a week, 3) The impact of student management is that the OSIS administrators become more punctual, independent, Solid coordination between the Principal, Deputy Head of Student Affairs, OSIS Supervisor, and all Management, well-organized work program, The OSIS has become more creative, has a sense of responsibility, the OSIS Management has become more self-confident, more disciplined and brave.